Обґрунтування рецептурного складу фонданів спеціального призначення - Блощинська (Дудкіна), Олена Олександрівна; Губенко, Станіслава Олегівна; Гавриш, Андрій Володимирович; Нєміріч, Олександра Володимирівна (My University, 2015)
Подано результати практичних досліджень з обґрунтування рецептурного складу під час виготовлення фонданів спеціального призначення як нової гарячої солодкої страви, що дозволяє розширити асортимент страв для окремих верств населення у закладах ресторанного господарства. This article is dedicated to the research and to argument of selection of raw materials for fondans, for special purposes. A significant segment of products presented as hot desserts, are in high demand and popularity among different age groups. This leads to the further development of improvement the technological process production of recipe compositions using mathematical modeling. Diversification of raw materials for fondant will improve or modify the organoleptic quality indicators of the dessert, such as taste, flavour, color, appearance and perfect the nutritional and biological value of dessert. Therefore, it is reasonable to conduct the experimental research and develop the technical documentation for new types of fondant desserts with alternative raw materials.
Keywords: фондан; fondans; рисове борошно; rice flour; целіакія; celiac disease; кафедра технології ресторанної і аюрведичної продукції; кафедра готельно-ресторанної справи